El uso de las lenguas indígenas en el teatro colonial. El ejemplo del quechua (Estudios) - Trucharte, Marina (2014)
In this article the author looks at how the quechua language was used in the arts, and particularly in the dramatic art, during colonial period. It concentrates on its utilization by the Spanish clergy and the reasons for this usage. We see that the knowledge of Quechua, or runasimi, was a necessity for the colonial authorities, especially in order to pass on the foundations of the Catholic religion to the natives. The Spanish religious also used the language of the Incas on their theater of evangelization; they translated Spanish works into Quechua and presented them to the natives. They thus used theater as an educational instrument and to diffuse the values of the Spanish Empire. The Quechua language was then used by Peruvian playwrights to create original plays, a true stylistic and cultural mixture of the Spanish and inca civilizations. We shall try to see what the peculiarities of these works and their real and supposed objectives were. Finally, we shall present the impact which they had on the colonial population and the authorities.